PROSES BERMAIN MATEMATIKA AWAL DI RA MIFTAHUL HUDA NGASEM NGAJUM-MALANG - Wahyuni, Sri; Sari, Ratih Permata (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2019)
The mathematical play process aims to describe the difficulties encountered while playing mathematics and describe the success stages of the initial mathematical play process. The research method used is descriptive-qualitative approach. Data collection techniques used are observation, interviews, and documentation. The results showed that the early mathematical play process emphasized cognitive development in early childhood. Learning difficulties faced by early childhood through internal and external factors. The application of the first stage of teacher is able to master the basic concepts of mathematics, the second stage of the level of analysis of children in the process learning mathematics is seen in play activities and the third stage provides motivation, guidance, direction according to the needs of children through the empowerment of learning media resources related to the initial mathematical material. Based on the results of analysis it can be concluded that there is a successful process of early mathematics learning at RA Miftahul Huda Ngasem